Aerogels: Aerogels from CdSe/CdS Nanorods with Ultra‐long Exciton Lifetimes and High Fluorescence Quantum Yields (Adv. Mater. 40/2015). (21st October 2015) - Sánchez‐Paradinas, Sara; Dorfs, Dirk; Friebe, Sebastian; Freytag, Axel; Wolf, Andreas; Bigall, Nadja C.
<x xml:space="preserve">Abstract</x> The fabrication of gels from semiconductor nanoparticles by means of a controlled and optimized destabilization process is investigated by N. C. Bigall and co‐workers on page 6152. Aerogels with high photoluminescence quantum yield and ultra‐long radiative lifetimes are fabricated from CdSe/CdS seeded nanorods. It is shown that excited electrons can be delocalized within the aerogel monolith while, at the same time, holes stay confined in the CdSe cores. This type of assembly of nanoparticles shows novel properties in comparison to those of the nanoparticle building blocks and of the bulk material.